One-Stage Augmentation Mastopexy: A Review of 1192 Simultaneous Breast Augmentation and Mastopexy Procedures in 615 Consecutive Patients. (July 2014) - Stevens, W. Grant; Macias, Luis H.; Spring, Michelle; Stoker, David A.; Chacón, Carlos O.; Eberlin, Seth A.
Background: Despite the increasing popularity of the combined augmentation mastopexy procedure among patients, the safety and efficacy of this surgery have been questioned by many surgeons. Objective: The authors investigated the safety and efficacy of the combined augmentation mastopexy procedure. Methods: The authors retrospectively reviewed the medical records of 615 consecutive patients who underwent combined augmentation mastopexy procedures at a single outpatient surgery center from 1992 through 2011. Patient demographics, operative and implant details, and long-term outcomes were analyzed. Rates of complications and revisions were calculated. Results: The most common complications were poor scarring (5.7%), wound-healing problems (2.9%), and deflation of saline implants (2.4%). Of the 615 patients evaluated, 104 (16.9%) elected to undergo revision surgery: 54 revision procedures were secondary to implant-related complications, and 50 were secondary to tissue-related complications. Our data compare favorably with previously reported revision rates for breast augmentation alone and mastopexy alone. Conclusions: With a skilled surgeon and proper patient selection, the combined augmentation mastopexy procedure can be safe and effective. Level of Evidence: 4